2007
DOI: 10.1097/mbc.0b013e328136c18a
|View full text |Cite
|
Sign up to set email alerts
|

Seminal thrombin-activatable fibrinolysis inhibitor: a regulator of liquefaction

Abstract: Several active components of the haemostatic system have been identified in human semen. Here we investigated the presence of thrombin-activatable fibrinolysis inhibitor (TAFI) in seminal plasma. Using an enzyme-linked immunosorbent assay, TAFI levels were measured in 36 semen specimens obtained from subfertile, normally fertile, fertile sperm donor and vasectomized individuals. TAFI was detectable in human semen. Its levels were highest in vasectomized individuals compared with the other groups, including a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For example, the serine protease plasmin (the activated form of plasminogen) is able to activate KLK11 in vitro (Luo et al, 2006). In addition to the proteins mentioned above, many of which are also expressed as blood plasma proteins, classic hemostatic factors may also contribute to seminal clotting and liquefaction (Lwaleed et al, 2004, 2005, 2007), including a major role for tissue factor (TF; thromboplastin) (Lwaleed et al, 2006; Fernández and Heeb, 2007). Consistent with an important role of TF in seminal fluid, levels of this protein are much higher in semen (average of 21 ng/ml; Fernández and Heeb, 2007) than in blood (average of 85 pg/ml; Fernández et al, 1997).…”
Section: Functions Of Seminal Fluid Proteases and Their Inhibitorsmentioning
confidence: 99%
“…For example, the serine protease plasmin (the activated form of plasminogen) is able to activate KLK11 in vitro (Luo et al, 2006). In addition to the proteins mentioned above, many of which are also expressed as blood plasma proteins, classic hemostatic factors may also contribute to seminal clotting and liquefaction (Lwaleed et al, 2004, 2005, 2007), including a major role for tissue factor (TF; thromboplastin) (Lwaleed et al, 2006; Fernández and Heeb, 2007). Consistent with an important role of TF in seminal fluid, levels of this protein are much higher in semen (average of 21 ng/ml; Fernández and Heeb, 2007) than in blood (average of 85 pg/ml; Fernández et al, 1997).…”
Section: Functions Of Seminal Fluid Proteases and Their Inhibitorsmentioning
confidence: 99%
“…Both thrombin-antithrombin complexes and D-dimers have been measured in human semen [24]. Furthermore, we recently demonstrated the presence of TAFI in semen [17]. Thrombomodulin has also been found in urine [25][26][27].…”
Section: Discussionmentioning
confidence: 96%
“…We recently [17] identified TAFI in human semen and suggested that semen-derived TAFI may play a role in the protection of the seminal clot against fibrinolysis. For TAFI to inhibit blood fibrinolysis it has to be activated by thrombin, thrombin/thrombomodulin complex or plasmin [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, TAFI was found in human seminal plasma, where TAFI might be involved with the coagulation and liquefaction of human semen for the protection of the seminal clot against lysis. 25 Further insights into the biology of TAFI can be gained by measuring the TAFIa and TAFIai activation isoforms. The activation of TAFI is regulated by a number of factors including expression In the present studies, TAFIa/ai ELISA was used for the specific quantitation of TAFIa and TAFIai antigens in plasma.…”
Section: +mentioning
confidence: 99%